Factors influencing farmers practices in using pesticide for vegetable cultivation at sadar upazila of Gazipur district in Bangladesh - Yeasmin, F; Yasmin, S; Nahar, K (Progressive Agriculture, 2018)
The focus of the study was to determine the pesticide control measures practiced by the farmers in Sadar Upazila of Gazipur district of Bangladesh. Data were collected through personal interview during the period of November 2016 to March 2017. Total numbers of 90 respondents were selected as the sample of the study. Safety measures were not taken by most of the respondents. Education, training, experience, extension contact and knowledge towards practices of pesticide use had significant positive relationships (at 1% level) with the pesticide use for vegetable cultivation. Age, farm size, family size, farming experience and annual income of the respondents had no significant relationships with the pesticide use for vegetable cultivation. "Hand sprayers are used for pesticide application in your plot" was identified as the first highest scores (PPI = 296) and "Use of appropriate pesticide" was the second highest scores (PPI = 287) and "Use Knapsack Sprayer for pesticide application" achieved the lowest scores (PPI = 2) about their use of recommended pesticides and methods. The above findings suggested that the farmers did not use knapsack sprayer. Applicators usually spray their field with different types of hand sprayer machine for vegetable cultivation. In this regard "Take bath right after spraying" (PPI = 299) was the highest and "Use Shoes/Head cover/Glasses when applied pesticide" (PPI =73) was the lowest scores. Majority of the farmers were aware about safety measures about ‘after using pesticide they took bath’, but most of the farmers were not aware of using of shoes, head cover and glasses while using pesticide in their field. Progressive Agriculture 29 (3): 259-266, 2018